Interface driven magnetoelectric effects in granular CrO2 - Bajpai, Ashna; Borisov, Pavel; Gorantla, S.; Klingeler, Rüdiger; Thomas, J.; Gemming, T.; Kleemann, Wolfgang; Büchner, B. (epl, 2010)
Antiferromagnetic and magnetoelectric Cr2O3-surfaces strongly affect the electronic properties in half metallic CrO2. We show the presence of a Cr2O3 surface layer on CrO3 grains by high-resolution transmission electron microscopy. The effect of these surface layers is demonstrated by measurements of the temperature variation of the magnetoelectric susceptibility. A major observation is a sign change at about 100 K followed by a monotonic rise as a function of temperature. These electric field induced moments in CrO3 are correlated with the magnetoelectric susceptibility of pure Cr2O3. This study indicates that it is important to take into account the magnetoelectric character of thin surface layers of Cr2O3 in granular CrO2 for better understanding the transport mechanism in this system. The observation of a finite magnetoelectric susceptibility near room temperature may find utility in device applications.
Im Titel ist 2 tiefgestellt
Gesehen am 18.11.2022